Human liver tissue transcriptomics revealed immunometabolic disturbances and related biomarkers in hepatitis B virus-related acute-on-chronic liver failure - Yang, Luo; Zhen, Limin; Li, Zhihui; Zhu, Shu; Xu, Wenxiong; Luo, Qiumin; Peng, Liang; Xie, Chan (Frontiers in Microbiology, 2022)
Acute-on-chronic liver failure (ACLF) is a major cause of liver-related death worldwide, but its key pathological features remain incompletely defined. This study aimed to reveal the molecular basis of hepatitis B virus-related ACLF (HBV-ACLF) by transcriptome sequencing of human liver tissue. A total of 18 human liver tissues from patients with different stages of HBV-related disease were collected for RNA sequencing, and liver tissues from patients and mouse models with ACLF were used for subsequent validation. Specifically, 6853 differentially expressed genes (DEGs) and 5038 differentially expressed transcripts were identified in patients with ACLF compared to patients with chronic hepatitis B (CHB) and normal controls (NCs). Investigation of functional by KEGG pathway enrichment analysis revealed prominent immune and metabolic dysregulation at the ACLF stage. We found that the key genes FGF19, ADCY8 and KRT17, which are related to immunometabolic disturbances, were significantly upregulated in the progression of ACLF. The three key genes were validated in human and mouse samples, indicating their prognostic and therapeutic potential in ACLF. In summary, our work reveals that immunometabolic disorder is involved in HBV-ACLF pathogenesis and indicates that FGF19, ADCY8 and KRT17 may be sensitive biomarkers for HBV-related ACLF.